Budaya Srawung sebagai Potret Toleransi Beragama dan Bersuku untuk Meredam Konflik di Kota Semarang - Stefanus Wawan Setiawan; Rispritosia Sibarani (Anthropos: Jurnal Antropologi Sosial dan Budaya (Journal of Social and Cultural Anthropology), 2021)
This paper aims to describe and analyze the ideological / cultural hegemony problems that occur in Semarang. The tolerance behavior in Semarang is considered to be experiencing degradation. Nowadays problems and conflicts always arise related to tolerance. With the existence of mutually offensive cases, especially those that often occur in religious and multiethnic life. Then latent conflict in Semarang City needs to be handled seriously. One of the treatments is to develop local wisdom of Javanese culture; srawung. 'Srawung' is a Javanese term that means gathering or meeting conducted by more than one person or group, with togetherness and not concerned with different religious groups, then the relationship in building harmony and togetherness will be maintained in people's lives. This paper uses a qualitative research method with a qualitative descriptive approach. This research was examined using Public Space theory from Jurgen Habermas. The expectation of this research through Srawung culture is to become a bridge of harmony, bonding brotherhood, can reduce conflicts between religious communities, and can be used as a reference solution for the problems of horizontal conflict that often occur in this country.